Implementasi Bahasa Strategi Branding Produk untuk Meningkatkan Daya Saing Penerbit - Rawuh Yuda Yuwana; Sri Ananda Pertiwi; Acep Fatchuroji (AKSELERASI: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to implement strategic branding language to enhance the competitiveness of an independent publishing house, namely Akselerasi Karya Mandiri Publisher, located in Merauke, South Papua. The activity is grounded in the partner’s limited utilization of language as a strategic branding instrument in promoting publishing products, which has constrained market visibility and competitiveness. The program employed a participatory and practice-based mentoring approach, encompassing needs assessment, conceptual training, assisted development of branding language, initial implementation, and reflective evaluation. The results indicate a significant improvement in the partner’s understanding of the strategic role of language in shaping publisher identity and brand image, as well as the production of more structured, consistent, and value-oriented branding language for publishing products. Initial implementation of the revised branding language in promotional media demonstrated positive changes in message delivery and strengthened product identity. This activity contributes to enhancing the partner’s capacity to manage branding language independently and sustainably, while also supporting the development of the local literacy ecosystem. Therefore, the implementation of strategic branding language serves as a relevant empowerment approach for independent publishers seeking to improve competitiveness in the digital literacy era.